Magnetization reversal of antiferromagnetically coupled perpendicular anisotropy films driven by current. Issue 5 (May 2018) - Zhao, X.T.; Zhao, Y.Q.; Liu, W.; Dai, Z.M.; Wang, T.T.; Zhao, X.G.; Zhang, Z.D.
Abstract: By inserting an ultrathin Pt layer at Co/Ru interface, we established antiferromagnetic coupling with out-of-plane magnetization in Co/Ru/Co film stacks fabricated by sputtering. To achieve configuration suitable for free layer, the magnetic properties of the stacks have been investigated by changing the thickness of Co, Ru and Pt layers using an orthogonal wedges technique. It is found that magnetic properties for upper Co layer thinner than 0.5 nm are sensitive to little change in Ru thickness. Improving continuity of upper Co layer by slightly increasing the thickness can effectively increase the squareness of minor loop. The switching magnetization of synthetic antiferromagnetic (SAF) structure is achieved by DC current under an in-plane static magnetic field of ± 500 Oe. This structure is very promising for free layer in spintronic application.